Analisis Implementasi Pemungutan Ppn Atas Transaksi Digital Di Indonesia Dalam Rangka Peningkatan Penerimaan Pajak - Imaniar, Emita Ika; Kumala, Ratih (Jurnal Ilmu Administrasi Publik, 2024)
Currently the Directorate General of Taxes needs a special strategy to collect revenue from the tax sector, because the impact of the COVID-19 pandemic has also attacked the economic sector and contracted income from several other business sectors, so that the DJP has lost some potential tax revenue from sectors affected by the pandemic. So it is necessary to expand other tax bases which could provide potential state revenue. The Minister of Finance responded freely to the situation where foreign digital companies enjoyed a significant market presence in Indonesia, supported by the COVID-19 pandemic situation which encouraged people to actively utilize digital technology to meet their daily needs. The aim of this research is to analyze the implementation of VAT collection on digital transactions in Indonesia. Implementation of policies  Digital VAT collection is analyzed using Charles Edward III's theory, using four indicators of successful policy implementation, namely communication, resources, disposition/attitude of implementers and organizational structure. Apart from that, researchers also analyzed the obstacles and efforts in implementing digital VAT collection policies in Indonesia. The research method used is a qualitative approach with descriptive research type. Data collection techniques in this research were literacy studies, interviews and documentation. The results of this research explain that the implementation of the VAT collection policy on digital transactions in Indonesia has gone quite well based on the four indicators in George Charles Edward III's theory. This success is proven by the realization of state revenue from PMSE VAT collection of 8.1 trillion rupiah in a 2 year period, from August 2020 to August 2022. Apart from that, the Directorate General of Taxes is also still committed to remaining active in collaborating by appointing PMSE business actors. as a collector. Regarding obstacles, DJP faces several obstacles in implementing this policy, but continues to strive to overcome existing obstacles.